Newcastle disease vaccination: From technology to poverty reduction - Young, J.; Grace, Delia; Young, M.; Alders, Robyn G.; Kibaya, A.; Msami, H.; Bagnol, B. (International Livestock Research Institute, 2012)
Newcastle disease (ND) is a major constraint to village chicken production in Africa. In endemic areas up to 50-100% of the village flock is lost annually. Women poultry-keepers lose assets, income and ability to feed their families. Vaccines are highly effective, yet use in villages is low and little is known about the reasons for this. In 2003-2005 a project worked to promote the use of the I-2 ND vaccine in Chamwino District, Tanzania. This thermotolerant vaccine, developed by the University of Queensland, is affordable, effective, and easy to administer. Five years later, we investigated vaccine uptake. Villages were stratified by delivery system (project, and active, inactive, and no extension), 2 were randomly selected from each strata, and households randomly sampled. Questionnaires (n=456), conjoint analysis (n=455), participatory appraisal (n=100 participants) and gender-specific focus group discussion (n=206) were used to assess social, cultural and economic determinants of vaccination. Losses from ND were high: households kept on average 15 poultry, and had lost 20 in the last year, 15 from ND. Only 1/3 had vaccinated in the last year. Conjoint analysis found distance and price were more important vaccine attributes than effectiveness or bundled services. Wealth, gender, knowledge, and disease impacts all influenced uptake, but more important were previous experiences of vaccination and the delivery system available. With adequate systems, vaccination delivered major benefits; with poor systems vaccination was associated with increased losses. In the study area, the major driver for vaccine uptake failure is not poultry-keepers but the services available to them. Given active extension, well-trained vaccinators, and participatory service delivery, ND vaccine can bring important benefits to poultry health and livelihoods of the poor.